A critical review on the role of abiotic factors on the transformation, environmental identity and toxicity of engineered nanomaterials in aquatic environment. (1st March 2022) - Kansara, Krupa; Bolan, Shiv; Radhakrishnan, Deepika; Palanisami, Thava; Al-Muhtaseb, Ala'a H.; Bolan, Nanthi; Vinu, Ajayan; Kumar, Ashutosh; Karakoti, Ajay
Abstract: Engineered nanomaterials (ENMs) are at the forefront of many technological breakthroughs in science and engineering. The extensive use of ENMs in several consumer products has resulted in their release to the aquatic environment. ENMs entering the aquatic ecosystem undergo a dynamic transformation as they interact with organic and inorganic constituents present in aquatic environment, specifically abiotic factors such as NOM and clay minerals, and attain an environmental identity. Thus, a greater understanding of ENM-abiotic factors interactions is required for an improved risk assessment and sustainable management of ENMs contamination in the aquatic environment. This review integrates fundamental aspects of ENMs transformation in aquatic environment as impacted by abiotic factors, and delineates the recent advances in bioavailability and ecotoxicity of ENMs in relation to risk assessment for ENMs-contaminated aquatic ecosystem. It specifically discusses the mechanism of transformation of different ENMs (metals, metal oxides and carbon based nanomaterials) following their interaction with the two most common abiotic factors NOM and clay minerals present within the aquatic ecosystem. The review critically discusses the impact of these mechanisms on the altered ecotoxicity of ENMs including the impact of such transformation at the genomic level. Finally, it identifies the gaps in our current understanding of the role of abiotic factors on the transformation of ENMs and paves the way for the future research areas. Highlights: ENM disposed in the aquatic environment interact with abiotic factors – clay and NOM. Interactions of ENM with clay and NOM influence their transformation in aquatic media. ENM attain a new environmental identity after interacting with abiotic factors. The ecotoxic potential of ENM is governed by their interaction with abiotic factors.